CTLA-4 Facilitates DNA Damage–Induced Apoptosis by Interacting With PP2A - Yan, Qiongyu; Zhang, Bin; Ling, Xi; Zhu, Bin; Mei, Shenghui; Yang, Hua; Zhang, Dongjie; Huo, Jiping; Zhao, Zhigang (Frontiers in Cell and Developmental Biology, 2022)
Cytotoxic T-lymphocyte–associated protein 4 (CTLA-4) plays a pivotal role in regulating immune responses. It accumulates in intracellular compartments, translocates to the cell surface, and is rapidly internalized. However, the cytoplasmic function of CTLA-4 remains largely unknown. Here, we describe the role of CTLA-4 as an immunomodulator in the DNA damage response to genotoxic stress. Using isogenic models of murine T cells with either sufficient or deficient CTLA-4 expression and performing a variety of assays, including cell apoptosis, cell cycle, comet, western blotting, co-immunoprecipitation, and immunofluorescence staining analyses, we show that CTLA-4 activates ataxia–telangiectasia mutated (ATM) by binding to the ATM inhibitor protein phosphatase 2A into the cytoplasm of T cells following transient treatment with zeocin, exacerbating the DNA damage response and inducing apoptosis. These findings provide new insights into how T cells maintain their immune function under high-stress conditions, which is clinically important for patients with tumors undergoing immunotherapy combined with chemoradiotherapy.